An investigation on the effectiveness of cost cutting techniques on financial performance of an organisation: a case of Zinara - Mukwani, Loveness (Midlands State University, 2018)
The current study was carried out to investigate on the efficacy of the cost cutting measures implemented at ZINARA in an attempt to enhance the financial performance of the organisation. The researcher opted for a descriptive research design which was effectively coalesced with a qualitative research approach. A systematic sampling technique was employed to identify the 45 respondents to questionnaires and 5 interviewees from the management and employees of ZINARA. Results indicated that if carefully crafted and implemented, the measures which were employed by the organisation, particularly optimization of business processes and service outsourcing can go a long way in reducing the escalating expenses and improve their cash flow and financial position. Evidence gathered persuaded the researcher to recommend that management should move away from retrenchment where they risk losing experienced personnel. The research was successfully carried out with an originality value of 10%.